Actuating compact wearable augmented reality devices by multifunctional artificial muscle - Kim, Dongjin; Kim, Baekgyeom; Shin, Bongsu; Shin, Dongwook; Lee, Chang Kun; Chung, Jae Seung; Seo, Juwon; Kim, Yun Tae; Sung, Geeyoung; Seo, Wontaek; Kim, Sunil; Hong, Sunghoon; et al. (Nature Communications, 2022)
An artificial muscle actuator resolves practical engineering problems in compact wearable devices, which are limited to conventional actuators such as electromagnetic actuators. Abstracting the fundamental advantages of an artificial muscle actuator provides a small-scale, high-power actuating system with a sensing capability for developing varifocal augmented reality glasses and naturally fit haptic gloves. Here, we design a shape memory alloy-based lightweight and high-power artificial muscle actuator, the so-called compliant amplified shape memory alloy actuator. Despite its light weight (0.22 g), the actuator has a high power density of 1.7 kW/kg, an actuation strain of 300% under 80 g of external payload. We show how the actuator enables image depth control and an immersive tactile response in the form of augmented reality glasses and two-way communication haptic gloves whose thin form factor and high power density can hardly be achieved by conventional actuators.
Keywords: Augmented Reality; Equipment Design; Muscles; Shape Memory Alloys; Wearable Electronic Devices